1997
DOI: 10.1002/(sici)1096-8628(19970303)69:1<73::aid-ajmg14>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

New syndrome of spondylospinal thoracic dysostosis with multiple pterygia and arthrogryposis

Abstract: We describe a "new" syndrome of spondylospinal thoracic dysostosis with a short curved spine and fusion of the spinous processes, short thorax with "crab-like" configuration of the ribs, pulmonary hypoplasia, severe arthrogryposis and multiple pterygia, and hypoplastic maxilla and mandible in two siblings. This appears to be an autosomal recessive lethal trait. A literature review revealed two reports of four similar or related cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Previous to our case Turkel et al (1980); Chen et al (1984); and Johnson et al (1997) had reported eight patients with clinical features that strikingly resemble STD. Among the patients described, the oldest patient survived until 7 years of age (Turkel et al, 1980).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Previous to our case Turkel et al (1980); Chen et al (1984); and Johnson et al (1997) had reported eight patients with clinical features that strikingly resemble STD. Among the patients described, the oldest patient survived until 7 years of age (Turkel et al, 1980).…”
Section: Discussionsupporting
confidence: 52%
“…STD is a rare entity of the group of costovertebral dysplasias that includes subtle facial features such as hypoplastic maxilla and micrognathia (Johnson et al, 1997). The only constant feature mentioned in this syndrome is pterygia, and the other more frequent features are fusion of the vertebral body and spinal process, gracile/crowded ribs, lordotic spine, short thorax and neck, cystic hygroma, micrognathia, cleft soft palate, low set ears, pulmonary hypoplasia, and arthrogryposis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pena Shokeir phenotype/severe fetal akinesia conditions have been reported to have FCH (Elias, Boelen, & Simpson, ; Lazjuk, Cherstvoy, Lurie, & Nedzved, ). Lethal cerebroarteriodigital syndrome, a sporadic condition, may also present with FCH (Spranger et al, ), as has spondylovertebral hypoplasia conditions (Johnson, Keppen, Carpenter, Randall, & Newby, ; Krishnamurthy & Kapoor, ; Okumus et al, ; Turkel, Iseri, & Fujimoto, ). Bohring–Opitz syndrome (Bohring et al, ), maternal exposure to malathion (Lindhout & Hageman, ) and Peters' anomaly (Sulivan et al, ) have also been reported with FCH.…”
Section: Discussionmentioning
confidence: 99%
“…Lethal multiple pterygium syndrome (LMPS) was first reported by Gillin and Pryse-Davis (1976). It is usually inherited as an autosomal recessive trait, though X-linked recessive inheritance has been described (Chen et al, 1984;Hall, 1984;Van Regemorter et al, 1984;Tolmie et al, 1987;Johnson et al, 1997). The incidence and prevalence of this syndrome are unknown.…”
Section: Discussionmentioning
confidence: 99%